Maternal Hypothyroidism Increases the Risk of Attention-Deficit Hyperactivity Disorder in the Offspring - Peltier, Morgan R.; Fassett, Michael J.; Chiu, Vicki Y.; Getahun, Darios (American Journal of Perinatology, 2020)
Objective This study aimed to determine if hypothyroidism prior to, or during, pregnancy increases the risk of attention-deficit hyperactivity disorder (ADHD) in the child and how the association may be modified by preterm birth, sex of the child, and race-ethnicity.Study Design Data were abstracted from linked maternal–child medical records. Incidence rate differences (IRDs), adjusted hazard ratios (aHRs), and their 95% confidence intervals (CIs) were estimated to evaluate the association of maternal hypothyroidism with childhood ADHD risk. Stratified analyses were used to evaluate whether the association is affected by timing of first diagnosis, gestational age at birth (term vs. preterm), sex, and race-ethnicity.Results Hypothyroidism diagnosed prior to (IRD = 1.30), or during (IRD = 0.59) pregnancy increases the risk of ADHD in the children (aHR = 1.27; 95% CI: 1.15, 1.41, and 1.17; 95% CI: 1.00, 1.38). The association was strongest when diagnosed during the first trimester (IRD = 0.97 and aHR = 1.28; 95% CI: 1.04, 1.58). For children born preterm, there was significantly increased risk of ADHD if their mothers were diagnosed prior to (IRD = 3.06 and aHR = 1.43; 95% CI: 1.09, 1.88), but not during pregnancy. The effect of maternal hypothyroidism on increased risk of ADHD was stronger for boys (IRD = 1.84 and aHR = 1.26; 95% CI: 1.14, 1.40) than it was for girls (IRD = 0.48 and aHR = 1.19; 95% CI: 1.01, 1.40) and for Hispanic children (IRD = 1.60 and aHR = 1.45; 95% CI: 1.25, 1.68) compared with other race ethnicities.Conclusion Exposure to maternal hypothyroidism during the periconceptual period significantly increases the risk of ADHD and that the association varies with gestational age at delivery, child sex, and race-ethnicity.Key Points
Keywords: attention-deficit hyperactivity disorder; ADHD; hypothyroidism neurodevelopment; pregnancy; preterm birth; thyroid